1984
DOI: 10.1080/00039896.1984.10545849
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of Fatal Arsenic Poisoning Caused by Contaminated Drinking Water

Abstract: An outbreak of subacute poisoning occurred among nine members of a family; eight were ill with gastrointestinal symptoms, four developed encephalopathy, and two died. Abnormal liver function tests and leukopenia were common laboratory findings. Epidemiologic and environmental investigations traced the source of arsenic exposure to a farm well with water containing 108 ppm arsenic. The soil adjacent to the well was also contaminated with arsenic, possibly from waste pesticide. Presumably, arsenic gained access … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
1
4

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 3 publications
0
51
1
4
Order By: Relevance
“…Rodent models of arsenic exposure have also demonstrated disturbances in heme biosynthesis, characterized particularly by an increased urinary uroporphyrin excretion [26,27]. These observations explain the possible reason for 26% of our patients suffering from anaemia, also reported by previous workers [8,9]. However, we have seen a far higher prevalence of anaemia in the female patients than males, 26 out of 30; 14 of these female patients represented the underweight nutritional group.…”
Section: Number Of Patients With Clinical Symptomscontrasting
confidence: 54%
See 2 more Smart Citations
“…Rodent models of arsenic exposure have also demonstrated disturbances in heme biosynthesis, characterized particularly by an increased urinary uroporphyrin excretion [26,27]. These observations explain the possible reason for 26% of our patients suffering from anaemia, also reported by previous workers [8,9]. However, we have seen a far higher prevalence of anaemia in the female patients than males, 26 out of 30; 14 of these female patients represented the underweight nutritional group.…”
Section: Number Of Patients With Clinical Symptomscontrasting
confidence: 54%
“…These effects may be due to both a direct, cytotoxic or hemolytic effect on the blood cells [8,10] and a suppression of erythropoiesis [10]. The magnitude of exposure to patients examined by these researchers is not specified, although arsenic concentration in some of the wells in the area exceeded 1000 µg/L.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown that this metal has deleterious effects on the respiratory (Civantos et al, 1995;Dunlap, 1921;Lundgren, 1954;Morton and Caron, 1989;Pinto and McGill, 1953;Sandstrom et al, 1989), neurological (Armstrong et al, 1984;Blom et al, 1985;Civantos et al, 1995;Feldman et al, 1979;Lagerkvist and Zetterlund, 1994), and cardiovascular (Cullen et al, 1995;Jensen and Hansen, 1998;Lagerkvist et al, 1986Lagerkvist et al, , 1988 systems. The most common and well-characterized sign of As poisoning is the development of skin lesions and warts (Bickley and Papa, 1989;Dunlap, 1921;Holmqvist, 1951;Lagerkvist et al, 1986;Mohamed, 1998;Perry et al, 1948;Pinto and McGill, 1953).…”
Section: Arsenicmentioning
confidence: 99%
“…The haematopoietic system was also affected by both short-and long-term arsenic exposures. Anemia and leukopenia were common effects of poisoning and have been reported as resulting from acute, intermediate and chronic oral exposures (Armstrong et al, 1984). These effects might be due to a direct haemolytic or cytotoxic effect on the blood cells (Lerman et al, 1980).…”
Section: Total Leukocyte Count (Tlc)mentioning
confidence: 99%